1988
DOI: 10.1139/v88-386
|View full text |Cite
|
Sign up to set email alerts
|

The effects of aggregation, counterion binding, and added NaCl on diffusion of aqueous methylene blue

Abstract: DEREK G. LEAIST. Can. J. Chem. 66, 2452Chem. 66, (1988. A simplified version of the Harned conductimetric technique is used to measure binary diffusion of the self-associating dye methylene blue chloride in water at 25°C. As the dye concentration is increased from 0.0006 to 0.02 rnol dm-3, aggregation of the dye monomers and binding of the chloride counterions cause the dye's binary diffusion coefficient to drop from 0.83 x lo-' to 0.63 x lo-' m2 s-'. Ternary diffusion coefficients for aqueous methylene blue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 24 publications
4
27
0
Order By: Relevance
“…It was then observed that the MCMC method provided a highly accurate estimation of the diffusive front (i.e., grey value displacement) with a very good agreement with experimental results (deviation less than 3%, results not shown here). However, the predicted diffusion coefficient DB, was found to be equal to 3 × 10 −6 m 2 ·s −1 , which is not at all the order of magnitude of the expected diffusion coefficient of macromolecules into liquids (10 −11 to 10 −10 m 2 ·s −1 ) . This result suggested that at the outlet of the capillary, (i.e., during the first stages of the diffusion process), some convective effects existed and were dominating over the diffusion process.…”
Section: Modeling Methodsmentioning
confidence: 83%
See 1 more Smart Citation
“…It was then observed that the MCMC method provided a highly accurate estimation of the diffusive front (i.e., grey value displacement) with a very good agreement with experimental results (deviation less than 3%, results not shown here). However, the predicted diffusion coefficient DB, was found to be equal to 3 × 10 −6 m 2 ·s −1 , which is not at all the order of magnitude of the expected diffusion coefficient of macromolecules into liquids (10 −11 to 10 −10 m 2 ·s −1 ) . This result suggested that at the outlet of the capillary, (i.e., during the first stages of the diffusion process), some convective effects existed and were dominating over the diffusion process.…”
Section: Modeling Methodsmentioning
confidence: 83%
“…However, the predicted diffusion coefficient D B , was found to be equal to 3 3 10 26 m 2 Ás 21 , which is not at all the order of magnitude of the expected diffusion coefficient of macromolecules into liquids (10 211 to 10 210 m 2 Ás 21 ). 25,38,42 This result suggested that at the outlet of the capillary, (i.e., during the first stages of the diffusion process), some convective effects existed and were dominating over the diffusion process. As a consequence, Eq.…”
Section: Modeling Methodsmentioning
confidence: 93%
“…This procedure has been repeated for the different total volumetric flow rates resulting in an average diffusion coefficient of 6.6 ± 0.55 10 -10 m 2 s -1 , which is in the same order of magnitude compared to similar redox dyes from literature [32,36].…”
Section: Diffusion Coefficient Of Indigo Carminementioning
confidence: 99%
“…The microfluidic devices are fabricated by placing the modified poly(dimethyl siloxane) (PDMS) top component on the hydrogel filled SU-8 bottom component and curing in an oven at 60 °C for 24 h. [52] Before measuring the device, the channel is first flushed with water for at least an hour to ensure a swollen state of the hydrogel and removal of any residual nonreacted monomer. Two syringes connected to pumps, filled with deionized water and deionized water containing methylene blue [53] as contrast agent, respectively, were connected to the two inlets of the chip. It was found that the completely filled scaffold resulted in an always on state of the mixer, showing that the gel was not capable to shrink sufficiently to achieve a completely flat surface (vide supra).…”
Section: Mixing Behavior Of the Photoresponsive Micromixermentioning
confidence: 99%